1993
DOI: 10.1103/physrevlett.71.1316
|View full text |Cite
|
Sign up to set email alerts
|

Tau polarimetry with inclusive decays

Abstract: The spin asymmetry parameter A τ characterizing the angular distribution of the total hadron momentum in the decay of a polarized tau can be calculated rigorously using perturbative QCD and the operator product expansion. Perturbative QCD corrections to the free quark result A τ = 1/3 can be expressed as a power series in α s (M τ ) and nonperturbative QCD corrections can be expanded systematically in powers of 1/M 2 τ . The QCD prediction is A τ = 0.41 ± 0.02. In the decay of a high energy tau into hadrons, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Since the original and previous theoretical works in [1]- [5] and the ALEPH measurement [6], there has been an amount of progress both theoretically and experimentally in the determination of α s from tau decays. The theoretical progress resides mainly in a better understanding of the QCD perturbative and nonperturbative contributions to the inclusive hadronic width, as discussed in recent reviews [7]- [9] while the experimental one can be essentially due to the improved measurement of the leptonic width (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original and previous theoretical works in [1]- [5] and the ALEPH measurement [6], there has been an amount of progress both theoretically and experimentally in the determination of α s from tau decays. The theoretical progress resides mainly in a better understanding of the QCD perturbative and nonperturbative contributions to the inclusive hadronic width, as discussed in recent reviews [7]- [9] while the experimental one can be essentially due to the improved measurement of the leptonic width (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…10 Once again, as seen in the We now turn to some QCD applications of our PA approach. Let us first consider the R τ ratio 11 where R τ is defined as follows:…”
mentioning
confidence: 99%
“…If the r decays semileptonically, then ET = -5 [14] (note that if one could observe the fi then E = 1). In [14] it is shown that the inclusive hadronic decays of the T can give EL = -0.42 (h stands for inclusive hadron states).…”
mentioning
confidence: 99%
“…If the r decays semileptonically, then ET = -5 [14] (note that if one could observe the fi then E = 1). In [14] it is shown that the inclusive hadronic decays of the T can give EL = -0.42 (h stands for inclusive hadron states). If one analyzes the detailed structure of the hadronic decays one can obtain better results [15,16] but we will just use this number in our discussions to follow.…”
mentioning
confidence: 99%